Hyperbaric Oxygen Therapy Increases Brain-Derived Neurotrophic Factor as well as Decreases Systemic Immune-Inflammatory Index and Systemic Inflammatory Response Index in Autism Spectrum Disorder - Verna Biutifasari; Ni Komang Sri Dewi Untari; Pramita Anindya Nugraheni; Ronald Pratama Adiwinoto; Djatiwidodo Edi Pratiknya; Vendra Setiawan; Hartono Kahar; Betty Agustina Tambunan (The Indonesian Biomedical Journal, 2024)
BACKGROUND: Neuroinflammation and immune dysregulation are frequently viewed as contributing factors of autism spectrum disorder (ASD). Brain-derived neurotrophic factor (BDNF) is involved in the maintenance of neuron viability, as well as in neuron differentiation. Meanwhile, Systemic Immune-Inflammatory Index (SII) and Systemic Inflammatory Response Index (SIRI) are basic hematological indices used to assess inflammation and immune status. Hyperbaric oxygen (HBO) is known to enhance cerebral blood flow and reduce inflammation, however, not many studies have observed the its effect on BDNF level, SII, and SIRI in ASD subjects; therefore, this study was performed.METHODS: Fifteen ASD subjects were involved in this study and received HBO therapy 10 times within a 2-week period. The HBO therapy was performed by letting the subjects got into an isolated chamber filled with 100% oxygen and 1.3 ATA pressure for 60 minutes. Pre- and post-therapy blood samples were taken from subjects. BDNF level was measured with Enzyme Linked Immunosorbent Assay (ELISA), while neutrophils, monocytes, lymphocytes and platelets were measured by hematology analyzer for the calculation of SII and SIRI.RESULTS: Post-therapy BDNF level was higher than pre-therapy (1.84 ng/mL vs. 1.46 ng/mL; p=0.039). The increased in BDNF suggested reduced neuroinflammation and enhanced connections between neurons. Both post-therapy SII (672.4 vs. 359.4; p=0.005) and SIRI (1.3 vs. 0.7; p=0.009) were significantly lower than pre-therapy indexes. Decreased in SII and SIRI signified a reduction in neuroinflammation.CONCLUSION: HBO therapy increases BDNF level, also decreases SII and SIRI in ASD subjects. These results suggest that HBO has an effect on neuroinflammation, specifically in ameliorating inflammation.KEYWORDS: autism spectrum disorder, BDNF, SII, SIRI, hyperbaric oxygen therapy